Impact of perioperative red blood cell transfusion, anemia of cancer and global health status on the prognosis of elderly patients with endometrial and ovarian cancer - Anic, Katharina; Schmidt, Mona Wanda; Schmidt, Marcus; Krajnak, Slavomir; Löwe, Amelie; Linz, Valerie Catherine; Schwab, Roxana; Weikel, Wolfgang; Brenner, Walburgis; Westphalen, Christiane; Rissel, René; Hartmann, Erik Kristoffer; et al. (Frontiers in Oncology, 2022)
Introduction Perioperative red blood cell (RBC) transfusions have been associated with increased morbidity and worse oncological outcome in some solid neoplasms. In order to elucidate whether RBC transfusions themselves, the preoperative anemia of cancer (AOC), or the impaired global health status might explain this impact on patients with endometrial cancer (EC) or ovarian cancer (OC), we performed a retrospective, single-institution cohort study. Materials and methods Women older than 60 years with EC or OC were included. The influence of RBC transfusions, AOC, and frailty status determined by the G8 geriatric screening tool (G8 score), as well as the clinical-pathological cancer characteristics on progression-free survival (PFS) and overall survival (OS), was determined by using the Kaplan-Meier method and the Cox regression analyses. Results In total, 263 patients with EC (n = 152) and OC (n = 111) were included in the study. Patients with EC receiving RBC transfusions were faced with a significantly shorter 5-year PFS (79.8% vs. 26.0%; p < 0.001) and 5-year OS (82.6% vs. 25.7%; p < 0.001). In multivariable analyses, besides established clinical-pathological cancer characteristics, the RBC transfusions remained the only significant prognostic parameter for PFS (HR: 1.76; 95%-CI [1.01–3.07]) and OS (HR: 2.38; 95%-CI [1.50–3.78]). In OC, the G8 score stratified the cohort in terms of PFS rates (G8-non-frail 53.4% vs. G8-frail 16.7%; p = 0.010) and AOC stratified the cohort for 5-year OS estimates (non-anemic: 36.7% vs. anemic: 10.6%; p = 0.008). Multivariable Cox regression analyses determined the G8 score and FIGO stage as independent prognostic factors in terms of PFS (HR: 2.23; 95%-CI [1.16–4.32] and HR: 6.52; 95%-CI [1.51–28.07], respectively). For OS, only the TNM tumor stage retained independent significance (HR: 3.75; 95%-CI [1.87–7.53]). Discussion The results of this trial demonstrate the negative impact of RBC transfusions on the prognosis of patients with EC. Contrastingly, the prognosis of OC is altered by the preoperative global health status rather than AOC or RBC transfusions. In summary, we suggested a cumulatively restrictive transfusion management in G8-non-frail EC patients and postulated a more moderate transfusion management based on the treatment of symptomatic anemia without survival deficits in OC patients.